Using reference materials of blast furnace slag, steelmaking slag, converter slag and fused fluxes when developing a procedure for analysis of slag-forming mixtures using inductively coupled plasma atomic emission spectrometry - I. I. Chernikova; T. V. Kostrikina; K. V. Tyumneva; T. N. Ermolaeva (Стандартные образцы)
Introduction. Slag-forming mixtures play an important role in obtaining metal without non-metallic inclusions. Required properties of slag-forming mixtures (SFMs) directly depend on their chemical composition, that is why control of individual component content in a mixture is an important stage in the technological chain of metallurgical production. At the present time, it is a common practice to use inductively coupled plasma atomic emission spectrometry (ICP-AES for analyzing SFMs, requiring sample preparation by alloying with alkali fluxes, which makes it impossible to determine potassium and sodium oxides in a sample. That is why it is necessary to work out a procedure for simultaneous determination of calcium, silicon, magnesium, aluminium, potassium, and sodium oxides by the method of ICP-AES, which would include quantitative transferring of all components into a solution. For that purpose, it is suggested to use microwave digestion of samples in autoclaves.The purpose was to develop a procedure for simultaneous determination of specified components of SFMs using ICP-AES after transferring the sample into a solution in an autoclave under conditions of microwave heating, and to certify it reference materials of slag and fluxes.Materials and methods. Compositional analysis of slag-forming mixtures was conducted using an atomic emission spectrometer with inductively coupled plasma «iCAP 6500 Duo»; sample digestion was conducted with the use of the microwave system «ETHOS PLUS». The following brands of SFMs were chosen as research objects: Melubir 9563 and Accutherm ST-SP/235AL4D; AlsifluxGS-C7; SRCP015, SRCP173P. For calibrating the spectrometer and controlling correctness of determining the specified components, the following reference materials were used: reference materials of blast furnace slag, steelmaking slag, converter slag, and fused fluxes, which have close chemical composition.Research results. An ICP-AES analysis procedure has been developed for calibrating the spectrometer and controlling correctness of determining CaO, SiO2 , MgO, Al2 O3 , K2 O, Na2 O in reference materials of blast furnace slag, steelmaking slag, converter slag and fused fluxes, which allows to establish target components of SFMs quickly and reliably.